Association of Clock gene (turClock) Polymorphism with Growth and Reproductive Traits in Turkeys, Meleagris gallopavo - Adikari , A.M.J.B.; Xu, J.; Smith, E.J. (International Journal of Poultry Science, 2018)
Background and Objective: A study was conducted to test the hypothesis that differences in DNA sequence variations of turkey Clock gene may be associated with growth and reproductive traits. The turClock gene for DNA sequence variations was screened and evaluated the relationships among its haplotypes (based on haplogroups) with growth and reproductive traits of the turkey. Methodology: A total of 290 birds including hybrid turkeys and seven different varieties of heritage turkeys were used. DNA sequences of turClock gene (24.6 kb) were screened by re-sequencing of individual amplicons. Haplogroups were determined based on the output from Visual Haplotypes and data were analyzed to find out the associations between genotype and phenotypic traits. Results: Twelve SNPs, including five, four and three in introns 6, 9 and 16 respectively, were identified in the turClock gene. Reported SNPs were not in the Hardy-Weinberg Equilibrium (HWE) (p≤0.05). Linkage disequilibrium (D‘) among SNPs ranged from 0.05-1.00. Pairwise fixation index (FST) ranged from 0.03-0.90. Five haplogroups were developed from 12 SNPs. Haplogroups frequencies ranged from 0.03-0.93, were significantly associated with body weight (BW) at 309 days of age, feed conversion ratio (FCR) for the periods of 34-68 and 69-159 days, egg production and average egg weight (p≤0.05). Conclusion: The haplogroups of the turClock gene are associated with growth and reproductive traits. DNA sequence variations of Clock genes at the nucleotide and haplotype levels are associated with differences in performance traits. The genomic information described in the present study would be valuable for future association studies between Clock gene and other economically important traits in the turkey using a candidate gene approach.